The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1016/j.mambio.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Landscape genetics of mountain lions (Puma concolor) in southern Brazil

Abstract: a b s t r a c tIt is suggested that mountain lions have suffered a bottleneck and lost their genetic diversity in an area in southern Brazil. In this study, we correlated landscape connectivity and patterns of gene flow to identify landscape permeability and possible sources of migrants for the population of mountain lions in southern Brazil, using circuit theory. Population structure was analyzed with Bayesian methods, and density and parentage relationships were also estimated, to evaluate the population gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…Finally, it should be added that a recent study of Tableland pumas found that this population has gone through a bottleneck (Castilho et al, 2011), corroborating the evidence of range reduction and posterior expansion as discussed. The recolonization of the puma was partially a product of the conservation policy that provided full protection status to the Atlantic forest.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Finally, it should be added that a recent study of Tableland pumas found that this population has gone through a bottleneck (Castilho et al, 2011), corroborating the evidence of range reduction and posterior expansion as discussed. The recolonization of the puma was partially a product of the conservation policy that provided full protection status to the Atlantic forest.…”
Section: Resultssupporting
confidence: 76%
“…Pumas shot while attacking livestock, consisted of males, females, adult, subadults, and young. Latter, a larger sample of 37 skin samples from wild pumas poached after depredation was obtained by Castilho et al (2011) on livestock from the studies in SC. Sheep flocks were the most abundant vulnerable livestock, and were prior to puma recolonization, raised free-ranging, with only two out of twelve surveyed ranches having them corraled at night .…”
Section: Direct Evidence Of Puma Recolonization Collected In S Brazilmentioning
confidence: 99%
“…Each micro-satellite locus was individually amplified in PCR reactions, according to Castilho et al , (2011). Allele sizes were defined by separating the amplification products on 6% polyacrylamide gels together with a 25 bp marker ladder.…”
Section: Methodsmentioning
confidence: 99%
“…The giant river otter Pteuronura brasiliensis (Gmelin, 1788) disappeared from this region in the 1950s, as has the bush dog Speothos venaticus (Lund, 1842), which probably occurred in southern Brazil and northeastern Argentina in the past (Fontana et al 2003). Mountain lions Puma concolor ( Linnaeus, 1771) persist in some parts of the region, although probably in very low abundance (Mazzolli 1993, Castilho et al 2010. Thus, this assemblage of carnivores probably lives in a state of "mesopredator release" (Crooks and Soulé 1999), most likely without the effect of predators regulating their populations.…”
Section: Introductionmentioning
confidence: 99%